Backstepping-based Super-Twisting Sliding Mode Control for a Quadrotor Manipulator with Tiltable Rotors - Shilin Yi; Keigo Watanabe; Isaku Nagai (Journal of Robotics and Control (JRC), 2022)
Designing a robust controller is very important in the control of outdoor unmanned aerial vehicles. This paper presents the design procedures and implementation of super-twisting sliding mode controller, which is a robust nonlinear controller. The robust controller is applied to an over-actuated quadrotor manipulator with four tiltable rotors. A serial manipulator with two links is mounted on the bottom of the quadrotor. The quadrotor possesses the property of decoupling its position and orientation. The main contribute of this paper is that a super-twisting sliding mode controller in vector form is designed and applied to the control of an over-actuated quadrotor manipulator. Another contribution of this paper is that the stability of the closed-loop system is proved by utilizing the Lyapunov stability theory. It is confirmed that the performance of the super-twisting sliding mode controller is superior to that of the conventional backstepping controller in terms of convergence rate and accuracy by simulations.